2019
DOI: 10.1021/acs.jced.8b01045
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium of Isobutyl Acetate + Isobutyl Alcohol + Imidazolium-Based Ionic Liquids at 298.15 and 308.15 K

Abstract: For separation of the azeotrope isobutyl acetate and isobutyl alcohol, imidazolium-based ionic liquids 1-hexyl-3-methylimidazolium hexafluorophosphate [Hmim][PF 6 ] and 1-octyl-3-methylimidazolium hexafluorophosphate [Omim][PF 6 ] were applied as the extractants in the extraction process. The liquid−liquid equilibrium (LLE) data for the ternary systems isobutyl acetate + isobutyl alcohol + ([Hmim][PF 6 ]/[Omim][PF 6 ]) were determined at temperature of 298.15 and 308.15 K. To evaluate extraction performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…The separation factor ( S ) and distribution coefficient ( D ) were applied to assess the suitability of the solvents sulfolane and DMSO, which are defined by eqs and , respectively, , where x 1 I , x 2 I , and x 3 I stand for the mole fractions of n -decane, 1-tetradecene, and 1-methylnaphthalene in the raffinate layer; x 1 II , x 2 II , and x 3 II indicate the mole fractions of n -decane, 1-tetradecene, and 1-methylnaphthalene in the solvent phase.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The separation factor ( S ) and distribution coefficient ( D ) were applied to assess the suitability of the solvents sulfolane and DMSO, which are defined by eqs and , respectively, , where x 1 I , x 2 I , and x 3 I stand for the mole fractions of n -decane, 1-tetradecene, and 1-methylnaphthalene in the raffinate layer; x 1 II , x 2 II , and x 3 II indicate the mole fractions of n -decane, 1-tetradecene, and 1-methylnaphthalene in the solvent phase.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Separation Factor and Distribution Coefficient. The separation factor (S) and distribution coefficient (D) were applied to assess the suitability of the solvents sulfolane and DMSO, which are defined by eqs 6 and 7, respectively, 32,33…”
Section: ∑ ∑ ∑mentioning
confidence: 97%
“…To evaluate the selectivity of EG extracting SBA from the mixtures of SBA + SBAC, the distribution coefficient ( D ) and separation factor ( S ) are used. They are defined as where i is the serial number of the components in the system, and i = 1, 2. x 2 II and x 2 I are the mole fractions of SBA in the EG-rich phase and the SBAC-rich phase, respectively. x 1 II and x 1 I are the mole fractions of SBAC in the EG-rich phase and the SBAC-rich phase, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, perstraction and membrane technology are limited by solution concentration and membrane fouling. , Liquid–liquid extraction as a separation technology for liquid mixtures has the advantages of simple operation, high separation efficiency, and low energy consumption and can be considered to separate water and butanol. There are several studies using this method to extract alcohols such as ethanol, methanol, , and isobutanol with excellent performance. In order to expand the development of 1-butanol extraction units, many basic measurements about water + 1-butanol + solvents have been done on the ternary liquid–liquid equilibrium system, and relevant extractants show good extraction efficiency. It was found that light alcohol can be extracted from the aqueous solution using a heavy alcohol .…”
Section: Introductionmentioning
confidence: 99%